2015
DOI: 10.3109/00952990.2014.998366
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid use and non-fatal overdose in a cohort of injection drug users

Abstract: Background There is growing concern regarding rising rates of prescription drug-related deaths among the general North American population as well as increasing availability of illicitly obtained prescription opioids. Concurrently among people who inject drugs (IDU), illicit prescription opioid use has increased while non-fatal overdose remains a major source of morbidity. Objectives This study aimed to evaluate whether the use of POs was associated with non-fatal overdose among IDU in Vancouver, Canada. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
17
2
Order By: Relevance
“…A previous study among these two cohorts noted a significant and positive relationship between PO use (i.e., injection and non-injection administration) and non-fatal overdose (Lake et al, 2015). In the current study, which controlled for non-injection PO use, we were able to identify some underlying trends in this previously noted association; namely, those who are using POs via non-injection and those who are injecting POs in addition to heroin may have accounted for the bulk of this group's risk for non-fatal overdose.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A previous study among these two cohorts noted a significant and positive relationship between PO use (i.e., injection and non-injection administration) and non-fatal overdose (Lake et al, 2015). In the current study, which controlled for non-injection PO use, we were able to identify some underlying trends in this previously noted association; namely, those who are using POs via non-injection and those who are injecting POs in addition to heroin may have accounted for the bulk of this group's risk for non-fatal overdose.…”
Section: Discussionmentioning
confidence: 86%
“…Past research has identified a significant positive association between PO use (i.e., oral, intranasal, or intravenous administration) and non-fatal overdose (Lake et al, 2015), and has also found that among PO-using young adults, non-fatal overdose is more common among those who inject POs (Silva et al, 2013b). However, few studies have explored a potential independent association between PO injection and non-fatal overdose among PWID.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Qualitative studies have also described associations between a shortage of prescription OPRs and increased illicit opioid use. [11,12] Injection of illicit heroin is 3 times more risky for overdose than injection of OPRs [13,14] and fentanyl 4 times more risky than heroin. [15] This potential shift from prescribed to illicit opioids could partially account for the observed increase in opioid overdose mortality, despite various efforts to implement changes in opioid prescribing and management by health systems and providers.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying explanation for this association requires further investigation. In particular, future research should examine the extent to which PO‐seeking behavior predicts riskier drug use practices that may increase the risk of overdose, such as polysubstance use, whether overdose predicts greater physician contact and PO‐seeking behavior or whether this association is explained by shared underlying risk factors for both PO‐seeking and overdose …”
Section: Discussionmentioning
confidence: 99%
“…PWID are known to commonly use POs for various reasons, including euphoria, pain relief, and management of withdrawal symptoms . Previous research suggests that PWID may be at a heightened risk of PO‐related harms, including overdose and infectious diseases such as HCV and HIV . Greater insight into the individual and social factors associated with seeking POs from physicians for nonmedical use may help to identify subpopulations of PWID who are at particularly high risk of PO‐related harms, providing critical knowledge to inform clinical and policy responses to PO misuse among this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%